Cross-border interactions and European identity. What fosters a strong sense of European belonging? - Henriques, J. (Comparative Sociology, 2021)
This article examines what types of cross-border interactions promote a stronger sense of European identity than national identity. Firstly, using data from the Eurobarometer survey a typology of cross-border practices is constructed and associated with different levels of European identity. Secondly, a qualitative study evaluates the life course of 36 individuals involved in a European binational relationship. Both interactions within and outside Europe are assessed. The findings show that three types of interactions might promote a strong identification as European. Intra-European Integrative interactions, involving a certain level of integration into the host society (in economic, educational and social systems) and associated with long-term stays. Multicultural interactions, involving a setting of shared activities and cooperation between individuals of several European nationalities. Outside Europe interactions, that put Europe at perspective between the “we” and the “others”. On the opposite, the effect of Non-Integrative (sojourns) and short-term stays might be negligible.